База данных оборудования Химической лаборатории - Бурыхина Е. С.; Волкова А. В.; Мартынко Е. А.; Павлов Д. И.; Пасюкова М. А.; Пуговкина Ю. С.; Мозгалева П. И. Полина Игоревна (Инициативные проекты, 2015)
Заглавие с титульного экрана